2016
DOI: 10.1111/ajo.12496
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, advice and attitudes toward women driving a car after caesarean section or hysterectomy: A survey of obstetrician/gynaecologists and midwives

Abstract: Clinicians frequently give advice about driving after surgery. This advice is inconsistent and many advise women not to drive for significant time periods. This study highlights the need for education and research about driving after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Strengths of this study include that it reflects current practice by specialist obstetricians in Australia and New Zealand in both urban and metropolitan areas. Our study was limited by the low response rate, however this was comparable to similar studies of the RANZCOG membership of 19–23%, and still represents a sizeable cohort [ 24 , 25 ]. Nonetheless, potential self-selection bias must be acknowledged as a limitation, particularly in light of this response rate; as with any survey, those that have greater interest or more strongly held views on a topic may be more inclined to complete the survey.…”
Section: Discussionsupporting
confidence: 62%
“…Strengths of this study include that it reflects current practice by specialist obstetricians in Australia and New Zealand in both urban and metropolitan areas. Our study was limited by the low response rate, however this was comparable to similar studies of the RANZCOG membership of 19–23%, and still represents a sizeable cohort [ 24 , 25 ]. Nonetheless, potential self-selection bias must be acknowledged as a limitation, particularly in light of this response rate; as with any survey, those that have greater interest or more strongly held views on a topic may be more inclined to complete the survey.…”
Section: Discussionsupporting
confidence: 62%
“…Several survey studies conducted in the last two decades inventorying convalescence recommendations following gynecological procedures demonstrated that there is substantial variation in convalescence advice given by health care providers and emphasized the need for unified convalescence guidelines [ 11 , 12 , 16 , 24 , 38 , 39 ]. However, we are not aware of research similar to our own, in which both input from experts as well as input from patients were used to generate convalescence recommendations.…”
Section: Discussionmentioning
confidence: 99%